2021
DOI: 10.1002/ejoc.202001532
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Formation of δ‐Lactones by Cerium‐Catalyzed Aerobic Coupling of β‐Oxoesters with Enol Acetates

Abstract: δ‐Valerolactone derivatives are formed by the cerium‐catalyzed, aerobic coupling of β‐oxoesters with enol acetates and dioxygen. The products possess a 1,4‐diketone moiety, thus, the conversion can be regarded as an Umpolung since the β‐oxoesters are oxidized to electrophilic α‐radicals. The transformation has similarities to the Baeyer‐Villiger oxidation (BVO) where the higher substituted residue migrates. An endoperoxidic oxycarbenium ion comparable to the Criegee intermediate in the BVO is proposed as a rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…Although the exact catalytic cycle of our reaction remains to be elucidated, we propose a plausible reaction mechanism based on our observations and known literature precedents (Figure 1B) [57,59,[66][67][68][69]. Under aerobic conditions the catalytic Ce III (OBn)L n species I (in situ derived by the reaction of CeCl 3 (Ce III L n ) with the substrate benzyl alcohol, BnOH) could be oxidized to L n Ce IV -OBn complex II [67][68][69]. During this process O 2 is converted into a superoxide radical anion O 2…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Although the exact catalytic cycle of our reaction remains to be elucidated, we propose a plausible reaction mechanism based on our observations and known literature precedents (Figure 1B) [57,59,[66][67][68][69]. Under aerobic conditions the catalytic Ce III (OBn)L n species I (in situ derived by the reaction of CeCl 3 (Ce III L n ) with the substrate benzyl alcohol, BnOH) could be oxidized to L n Ce IV -OBn complex II [67][68][69]. During this process O 2 is converted into a superoxide radical anion O 2…”
Section: Resultssupporting
confidence: 54%
“…As shown in Figure 1A, the absorption spectrum of the Ce IV (OBn)Cl n complex gradually shifted from λ max = 375 nm to λ max = 325 nm upon irradiation, which indicates a photoinduced Ce IV -OBn homolytic cleavage to generate a Ce III complex and a benzyloxy radical. Although the exact catalytic cycle of our reaction remains to be elucidated, we propose a plausible reaction mechanism based on our observations and known literature precedents (Figure 1B) [57,59,[66][67][68][69]. Under aerobic conditions the catalytic Ce III (OBn)L n species I (in situ derived by the reaction of CeCl 3 (Ce III L n ) with the substrate benzyl alcohol, BnOH) could be oxidized to L n Ce IV -OBn complex II [67][68][69].…”
Section: Resultssupporting
confidence: 53%
“…The product 12 was obtained in 66 % yield as a mixture of again two diastereoisomers ( dr 2 : 1). Since the oxidation is assumed to proceed via a planar radical species, [11c,d] neither diastereomeric ratio nor the relative configuration of compounds 10 and 12 must necessarily correlate. As a byproduct, γ‐lactone 11 was separated and isolated in 23 % yield as a single diastereoisomer which is obviously the result of intramolecular transesterification under the reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Employing O 2 balloon instead of (NH 4 ) 2 S 2 O 8 afford 2a in 68% ( Table 1 , entry 13). 16 Also, it was observed that the yields were less reproducible and varied about 15% upon using air as an oxidant ( Table 1 , entry 14). Irradiation with green LEDs did not lead to any product formation.…”
Section: Resultsmentioning
confidence: 99%